Maya Index dan Gambaran Habitat Perkembangbiakan Larva Aedes sp. Berdasarkan Endemisitas DBD di Kota Semarang Provinsi Jawa Tengah - Wahyu Praptowibowo (Jurnal Kesehatan Masyarakat (Undip), 2015)
Dengue haemorhagic fever (DHF) is an acute febrile disease caused by the dengue virus, which the human bloodstream through the bite of the Aedes aegypti. Semarang City in 2013 has 143 endemic villages, sporadic 33, and a potential one, and 2,364 cases with IR 134.09 / 100,000 inhabitants and CFR 1.14%. Maya Index (MI) can be used to evaluate the breeding place of mosquito eradication program (PSN). The purpose of this study was to determine the MI and density of larvae (HI, ABJ, CI, and BI) in endemic areas, sporadic, and potential. This study used an observational study in (cross-sectional). The sample in this study was taken as many as 300 house with simple random sampling method. Results showed that the rate of MI in the Mijen village 7% (low), 61% (medium), 32% (high) with a value of HI, ABJ, CI, and BI respectively 28%, 72%, 9.94%, 34. Bubakan village MI and 16% (low), 65% (medium), 19% (high) and HI (43%), ABJ (57%), CI (24.36%) and BI (57). While in the Polaman village MI 21% (low), 62% (medium), 17% (high) serata HI (35%), ABJ (65%), CI (20.87%), and BI (48). MI in endemic areas, sporadic, and their potential to have a high MI categories with larval density above the safe limit larval density (5%). PSN in endemic areas, sporadic, and potentially not run properly so it needs to be refreshing about the importance of the PSN in the prevention of dengue to the community in the sporadic village (Mijen), and in particular the potential for MI endemic villages with most high category.